Pengaruh promosi dan harga terhadap keputusan konsumen memilih jasa pengiriman - Nurhasanah Lubis; Rahmat Hidayat (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
The purpose of this study is to examine the effect of promotion and price on consumer decisions to choose delivery services on customers of PT. Tiki Jalur Nugraha Ekakurir (JNE) Medan Simpang Pelangi branch which started in July 2020, from a population of 3,000 people, a total sample of 97 people was obtained using the Slovin formula. The research instrument was tested by validity and reliability, data analysis and hypothesis testing using Multiple Linear Regression. The results of this study explain that promotion and price are factors that are considered by consumers to decide to choose JNE delivery services.